2020
DOI: 10.1002/ccr3.2654
|View full text |Cite
|
Sign up to set email alerts
|

A hidden cause of infertility in hypothyroid patients

Abstract: Methylene tetrahydrofolate reductase (MTHFR) gene mutations could be the cause of infertility in hypothyroid patients. Hence, it is worthy to screen for MTHFR gene mutations in infertile hypothyroid females and their partners if infertility persists after optimizing thyroid function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…A patient with a history of several miscarriages and hypothyroidism was treated with low dose aspirin, enoxaparin, LT4 (levothyroxine) and folic acid (5 mg/day), but she still faced two miscarriages at the 14th week of gestation. MTHFR testing identified the patient to be 1298A>C homozygous, and a change from folate to 5-MTHF and cobalamin in this patient resulted in a successful birth [86]. From these evidences, it is clear that MTHFR genotyping can help in the management of RPL and also in ensuring successful birth in pregnancy loss patients.…”
Section: Discussionmentioning
confidence: 82%
“…A patient with a history of several miscarriages and hypothyroidism was treated with low dose aspirin, enoxaparin, LT4 (levothyroxine) and folic acid (5 mg/day), but she still faced two miscarriages at the 14th week of gestation. MTHFR testing identified the patient to be 1298A>C homozygous, and a change from folate to 5-MTHF and cobalamin in this patient resulted in a successful birth [86]. From these evidences, it is clear that MTHFR genotyping can help in the management of RPL and also in ensuring successful birth in pregnancy loss patients.…”
Section: Discussionmentioning
confidence: 82%
“…One conference abstract ( 35 ) was excluded due to a lack of detailed information. A case report ( 7 ) and three ( 20 , 27 , 29 ) case-only studies were deleted. A case-control study was excluded because the data were unusable ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thyroid dysfunction is associated with several adverse perinatal outcomes in the mother and fetus, including infertility, miscarriage, hypertensive disorders, premature delivery, and decreased IQ in the offspring (3,4). Recently, several clinical and epidemiological studies have shown a relationship between methylenetetrahydrofolate reductase (MTHFR) polymorphisms and thyroid dysfunction (5)(6)(7). One of the publications reported that two women diagnosed with Hashimoto's thyroiditis suffered from infertility, and in both, MTHFR gene polymorphisms were identified (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that folliculogenesis, ovulation, fertilization, and ovarian reserves are adversely affected by hypothyroidism. It has been reported that the menstrual cycle of Hashimoto patients is adversely affected by the disease, and the incidence of infertility is higher in women with thyroid-related problems (5,6).…”
Section: Introductionmentioning
confidence: 99%